Male circumcision: summary of current clinical practice. Issue 3 (May 2014) - Modgil, Vaibhav; Rai, Sonpreet; Anderson, Paul C.B.
Abstract: In this review, the authors outline the medical indications and contraindications for adult male circumcision and discuss the growing evidence behind prophylactic circumcision. Copyright © 2014 John Wiley & Sons.